Governing sex: removing the right to take responsibility - Gillian Cowlishaw (International Journal for Crime, Justice and Social Democracy, 2014)
The Commonwealth Intervention of 2007 in the Northern Territory largely missed its ostensible aim of protecting sexually abused children, argues this essay which examines the relevant social, cultural and historical factors based on specific ethnographic work. Abstract The exposure in 2006 of horrific cases of sexual violence that allegedly characterised Northern Territory Aboriginal communities, evoked responses dominated by a predictable moral panic. Thus the Commonwealth Intervention of 2007 largely missed its ostensible aim of protecting sexually abused children. This essay moves beyond a moralising analysis to consider relevant social, cultural and historical factors based on specific ethnographic work. First I present a sense of some profound historically established differences and common themes in traditional Aboriginal and mainstream law in relation to the regulation of sexuality. Then I draw on evidence that Aboriginal people embraced the notion of ‘two laws’, even as the new era created profound difficulties in relation to sexual norms. Their ‘right to take responsibility’ (Pearson 2000) was further undermined by ‘Interventions’ that unashamedly diminished the ability of NT Aborigines to govern their own communities. Finally, mainstream institutions that are deeply engaged with Aboriginal communities need to consider the ways they may be perpetuating entrenched difficulties